North Atlantic Upper‐Ocean Hydrography During the Mid‐Pleistocene Transition Evidenced by Globorotalia truncatulinoides Coiling Ratios. Issue 4 (30th April 2019) - Kaiser, E. A.; Caldwell, A.; Billups, K.
Abstract: We use the coiling direction of planktic foraminifer Globorotalia truncatulinoides from four sites in the North Atlantic Ocean to assess spatial changes in upper‐ocean hydrography during the mid‐Pleistocene climate transition. Core top sediments indicate that the left‐coiling (sinistral) variety dominates regions characterized by a deep permanent thermocline as is characteristic of the subtropical gyre (Ocean Drilling Program Sites 1058 and Deep Sea Drilling Project Site 607) while right‐coiling (dextral) tests dominate the tropical (Ocean Drilling Program Site 925) and subpolar site (Deep Sea Drilling Project Site 552). We observe pronounced changes in the dominant coiling direction at the three subtropical to subpolar sites during the first of the more extreme glacial to interglacial transitions of the mid‐Pleistocene climate transition, Marine Isotope Stages (MISs) 22 to 21. We interpret these observations to reflect an increase in poleward warm water advection. The time interval between MIS 21 and MIS 15 is marked by a pronounced absence of sinistral tests. Because G. truncatulinoides (sinistral) is a deep dwelling species, their absence may be related to a decrease in dissolved oxygen during warm interglacial intervals. At the tropical site, precessional‐scale variations dominate changes in the coiling direction until midpoint interglacial MIS 23. Occurrences in the sinistral variety at this locale must be linked to cross‐equatorial water transport in the North Brazil Current, and precessional‐scale variations provide evidence for the sensitivity of the tropical regions to precessional forcing, at least until MIS 23 when this morphotype disappears in agreement with observation at other sites in the Atlantic Ocean. Key Points: Globorotalia truncatulinoides coiling ratios indicate increasing poleward warm water flow during the Marine Isotope Stages 22/21 transition Absence of G. truncatulinoides (sinistral) during Marine Isotope Stages 21–15 may reflect a response to dissolved oxygen levels Prior to the growth of large, 100 kyr paced ice sheets, the western tropical Atlantic is sensitive to precession forcing